Задача типа Гурса для уравнения высокого порядка - Юсубов, Ш.Ш. (Український математичний журнал, 2013)
Для рівняння високого порядку з домінуючою мішаною похідною розглянуто задачу типу Гурса без умов узгодження. Введено поняття фундаментального розв'язку, на основі якого одержано зображення розв'язку розглядуваної задачі. For a higher-order equation with leading mixed derivative, we consider the Goursat-type problem without consistency conditions. The notion of fundamental solution is introduced. By using this notion, we obtain a representation of the solution of the analyzed problem.